A conceptual framework for multidisciplinary design research with example application to agent-based modeling. (January 2022) - McComb, Christopher; Jablokow, Kathryn
Abstract : The design community traditionally excels at multidisciplinary research efforts, integrating work from social science, engineering, computer science, and other disciplines. Simultaneously, design is also developing as a discipline in its own right. In order to balance a multidisciplinary 1 tradition against consolidation around a core set of disciplinary foundations, the design community must make intentional decisions about engaging in multidisciplinary research. Towards this end, we propose the Degrees of Disciplinarity Framework, a lingua franca for describing varying relationships between disciplines in a given research effort. We also introduce research archetypes in relation to this conceptual framework and provide examples of the framework using agent-based modeling research in design. Further, we discuss implications of this framework for the education of future design practitioners and researchers. Highlights: The design community must intentionally consider multidisciplinarity. This work introduces the Degrees of Disciplinarity Framework. The framework is demonstrated through examples to agent-based modeling.